2008
DOI: 10.1111/j.1095-8649.2008.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression characterization of pepsinogen A in orange‐spotted grouper, Epinephelus coioides

Abstract: To understand the molecular mechanisms associated with digestive physiology of the stomach of orange-spotted grouper Epinephelus coioides, a cDNA library was constructed and 331 expressed sequence tags (EST) were generated and annotated. About 37Á17% of 226 identified ESTs were possibly related to digestive enzymes. Two type-A pepsinogens differing in putative isoelectric point were identified and characterized for the first time in E. coioides. The complete cDNAs were 1312 and 1314 bp in length, and the deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Quite possibly, because of the steric structure of the protein, the p I value may not be in complete accordance with its performance under chromatographic pH conditions (pH 7.0). p I values of other fish, such as three pepsinogens from Pacific bluefin tuna (5.69, 4.95, and 4.66) and pepsinogens A1 and A2 from orange-spotted grouper (4.41 and 5.17) , have been reported, whereas all of these p I values were deduced from amino acid sequence analysis based on molecular cloning. Compared with these, the p I values of snakehead pepsinogens were relatively lower.…”
Section: Resultsmentioning
confidence: 99%
“…Quite possibly, because of the steric structure of the protein, the p I value may not be in complete accordance with its performance under chromatographic pH conditions (pH 7.0). p I values of other fish, such as three pepsinogens from Pacific bluefin tuna (5.69, 4.95, and 4.66) and pepsinogens A1 and A2 from orange-spotted grouper (4.41 and 5.17) , have been reported, whereas all of these p I values were deduced from amino acid sequence analysis based on molecular cloning. Compared with these, the p I values of snakehead pepsinogens were relatively lower.…”
Section: Resultsmentioning
confidence: 99%
“…In fishes, a distinct nomenclature is currently used and three pepsinogen gene families have been described: Pgc, Pga1 and Pga2 [35][36][37][38]. We began by determining the repertoire of Pga, Pgf and Cym in tetrapods.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrapod aspartic proteases expressed almost uniquely in the stomach include Pga, Pgf, Pgc, Pgb and Cym [12,[32][33][34]. In fishes, a distinct nomenclature is currently used and three pepsinogen gene families have been described: Pgc, Pga1 and Pga2 [35][36][37][38]. We began by determining the repertoire of Pga, Pgf and Cym in tetrapods.…”
Section: (B) Duplication Pseudogenization and Loss Of Pepsinogen Genes In Vertebrate Speciesmentioning
confidence: 99%
“…The possibility that because of the steric structure of the protein, the pI value may not be in complete accordance with the performance of PG1 under chromatographic pH conditions was ascribed. On the other hand, pI values of three PGs from Pacific bluefin tuna (5.69, 4.95, 4.66;Tanji et al 2009), pepsinogen A1 and A2 from orange-spotted grouper (4.41, 5.17;Feng et al 2008), which were deduced from nucleotide sequences of cDNAs, have also been reported.…”
Section: Resultsmentioning
confidence: 93%